Perlindungan Hukum Terhadap Nasabah Mobile Banking dalam Transaksi Perbankan - Trisna Dewi, Ni Made (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
This essay discusses the legal protection for mobile banking custumers, because the mobile banking product as one of the delivery many benefits but contain many risk on the other side that could cause losses for the custumers. Therefore, the protection for mobile banking custumers is requiered in order to protect the rights of the custumers banking servise. The study was conducted to determine how the indonesian low and regulations that protect mobile banking custumers in banking transaction in case of the error transaction electronic in review of low number 11 of 2008 on information and electronic transactionsas well as the bankâ€™s responsibility for the mobile banking custumers in case of a transaction error. This study is a normative study with the literature research method to analyze the book of legal literature and the low number 8 of 1999 about the custumers protection, low number 10 of 1998 about the indonesia banking sistem, low number 11 of 2008 about the transaction and electronic information. The result showed that although there is no customers legislation that specificaly regulates mobile banking, but in indonesia positive legal order there are laws and regulation which has provided legal protection for mobile banking custumers. There are law number 11 of 2008 about information and electronic transaction as contained in article 1.2 and 3. The bankâ€™s responsibility to the custumer in case ofÂ error transaction. The loss is a proxy of fullfillment of one custumers protection law. Right to copensation in accordance with the treaty law in article 1313 civil law. Then the current legislation already includes aspects of legal protection for mobile banking custumers.